O papel da ANG-(1-7) na inativação de ERK 1/2 modulada por MKP-1 e IL-10 em aorta de camundongos - Lopes, Alejandra Sousa (2018)
The Renin Angiotensin System (RAS) plays a fundamental role in the regulation of blood pressure and electrolyte balance. The angiotensin peptide (ANG)-(1-7), bound to RAS, is predominantly generated in the vascular wall under two main pathways: through ANGII by the action of neutral endopeptidases and prolyl-endopeptidases or by ANGI action, by hydrolysis from Angiotensin converting enzyme 2 (ACE2). ANG-(1-7) binds to its receptor Mas coupled to G protein and acts mediating vasodilation, inhibiting cell growth, acting as an important antagonist of ANGII vascular actions (vasoconstriction and inflammation). Recently, studies have shown that ANGII effects can also be attenuated by regulatory cytokines such as Interleukin (IL)-10, which negatively modulates proinflammatory cytokine polysaccharides producers such as tumor necrosis factor-alpha and IL-6 and inhibits the production of reactive oxygen species (ROS), reducing inflammation and favoring vasodilation. Although ANG-(1-7) and IL-10 possess similar functions, in vascular aspects, the association of both factors is still unknown and it seems to be related with other two significant molecules: MAPK, extracellular signal-regulated kinase 1 and 2 (ERK 1/2), which can be stimulated by ANGII and prolongs vasoconstriction and also Phosphatase-1 of mitogen-activated proteins (MKP-1), an important phosphatase that has the primary function of inactivating MAPKs, and it is estimulated by IL-10. The objective of this work is to evaluate if ANG-(1-7) reduces ERK 1/2 activity due to stimulation of MKP-1 and IL-10, resulting in a decrease in vascular contraction. The present study was approved by the UFMT Animal Research Ethics Committee (23108.166477/2016-20). Aortic rings of male C57BL/6J mice, 10-12 weeks of age, were incubated with ANG-(1-7) [10μM] or vehicle for 5 min, to perform ANGII concentration-response curve in the presence or absence of Mas receptor antagonist (A-779, 100μM) and cAMP (Rp-cAMPs, 1μM). Vascular expressions of c-Raf, ERK1/2 and MKP-1 proteins were verified by Western Blot and immunocytochemistry in vascular smooth muscle cell culture (LVC), incubated individually or simultaneously with ANG-(1-7) [10μM] , ANGII [1μM] or vehicle for 5 min. IL-10 knockout animals, infused with ANGII (90ng / min) for 14 days were used to verify IL-10 protector effects. Finally, blood vessel from animals were incubated with ANG-(1-7) [10μM], or vehicle, for 12h, to evaluate indirect expression of IL-10. The results show that ANG-(1-7) reduces vascular contraction induced by ANGII, via activation of Mas receptors and cAMP formation. It was also demonstrated that ANG-(1-7) prevented ERK1/2 activation, possibly through activation of MKP-1 phosphatase, both in aortic tissue and in vascular smooth muscle cell culture. Other result found in this study was that IL-10-lacking animals, ANGII has exacerbated activity, presenting higher vascular contraction, probably due to the increase in ERK 1/2 expression. In addition, it was observed that vessels treated with ANG-(1-7) for 12 hours presented higher expression of STAT3, a crucial element in IL-10 signaling pathway. In conclusion, the results suggest that ANG-(1-7) stimulates the activity of MKP-1 and IL-10 signaling pathway, which inhibits the ERK1/2 phosphorylation and consequently contributes to the reduction of vascular contractile response.